Strategi Manajemen SDM dalam Meningkatkan Produktivitas pada PT Royal (Perusahaan Minuman Golongan B di Kota Manado) - Maatuil, Rexy Andalangi; Sulendorong, Putri Anggraini; Rengkeng, Meylia Frita; Phane, Peter (Indo Publishing, 2025)
In today’s increasingly competitive business environment, employee productivity has become a key determinant of organizational success, including in the beverage industry in Manado. This study aims to identify the human resource management (HRM) strategies implemented by PT Royal to enhance employee productivity. The research employs a descriptive qualitative method, with data collected through interviews, observations, and analysis of internal company documents. The findings reveal four main strategies implemented by the company: selective recruitment, continuous training, performance-based compensation, and the creation of a supportive work environment. These strategies have proven effective in improving employee motivation and loyalty, thereby maintaining the company’s overall productivity. The results highlight the importance of consistency in human resource development as a crucial factor for ensuring business sustainability and competitive advantage in the future.